FROM HOSPITAL READINESS TO PATIENT SAFETY: BUILDING LEADERSHIP CAPACITY FOR PATIENT SAFETY IN INDONESIA - Cyrus Y Engineer; Inge Dhamanti (Indonesian Journal of Health Administration, 2022)
The COVID-19 pandemic has had an influence on patient safety and quality of care. A research undertaken in numerous countries found a deterioration in the quality of care during the pandemic. Leaders can improve patient safety in any circumstances, pandemic or not, by building a safety culture, reacting to patient and staff concerns, supporting safety activities, and tracking progress. Good leadership is essential to the success of patient safety programs and improving patient safety. Leaders must first establish strategic priorities and plans for culture and infrastructure that will aid in increasing patient safety. They must also actively inquire about patient safety situations and regularly examine patient safety data. Leaders must also collect data in order to foster a culture of patient safety. It is also critical to ensure that adequate infrastructure is available to support safety activities. Leaders have an important role in establishing the optimal methods for enhancing patient safety. Measures and improvement actions are rarely carried out in many nations; thus, leaders must ensure and encourage quality and safety development. Leadership commitment is the foundation for both pandemic and non-pandemic safety and quality improvement. Patient safety recommendations frameworks can help leaders improve patient safety in their organizations.